Disease activity in patients with idiopathic inflammatory myopathy according to time since diagnosis and positivity to antisynthetase autoantibodies: data from the Myo-Spain registry - Tatiana Cobo-Ibáñez; Ivan Castellví; Ana Pros; Marta Domínguez-Álvaro; Laura Nuño-Nuño; Julia Martínez-Barrio; Vega Jovaní; Fredeswinda Romero-Bueno; Esther Ruiz-Lucea; Eva Tomero; Ernesto Trallero-Araguás; Javier Narváez; et al. (Arthritis Research & Therapy)
Abstract Objective To evaluate the main outcomes of disease activity and their association with other measures of activity, damage, and quality of life in patients with idiopathic inflammatory myopathy (IIM) according to time since diagnosis and positivity to antisynthetase autoantibodies (ASAs). Methods Cross-sectional multicenter study within the Spanish Myo-Spain registry. Cases were classified as incident (≤ 12 months since diagnosis) and prevalent. The main outcomes of disease activity were the Myositis Disease Activity Assessment visual analogue scale (MYOACT), the Manual Muscle Test 8 (MMT-8), physician global activity (PhGA), and extramuscular activity. Other measures of activity, damage, and quality of life included patient global disease activity, MYOACT muscular, creatine phosphokinase, Health Assessment Questionnaire, physician and patient global damage, global damage of the Myositis Damage Index, and the 12-item Short-Form Health Survey (SF-12). We analyzed associations using a multivariate generalized linear model and a simple linear regression model. Results A total of 554 patients with different diagnostic subgroups of IIM were included (136 incident and 418 prevalent cases), with 215 ASA-positive patients (58 incident and 157 prevalent cases). All measures of disease activity were higher in the incident cases (p < 0.05), except for MYOACT muscular and creatine phosphokinase, for which no differences were recorded in ASA-positive patients. No differences were found between incident and prevalent cases for measures of damage. Values for the physical component of the SF-12 were higher in the prevalent cases (p < 0.05). The multivariate model was initially significant overall for the main activity outcomes. Positivity to ASAs was positively and negatively associated with the MYOACT index and MMT-8, respectively (p < 0.05), although no association was recorded with PhGA and extramuscular activity. Prevalent cases were negatively associated with the main outcomes of activity, except with MMT-8, for which the association was positive (p < 0.05). Conclusions The main activity outcomes validated in polymyositis and dermatomyositis could also be used in other subtypes of IIM, such as antisynthetase syndrome. Recent diagnosis is associated with greater disease activity, as assessed based on these activity outcomes. PhGA and extramuscular activity are not modified by ASA positivity, thus supporting their preferred use for assessing treatment response in IIM with ASAs.